ANALISIS PENGARUH KUALITAS LAYANAN, STRATEGI KEY OPINION LEADER DAN PROMOSI DIGITAL TERHADAP REPURCHASE INTENTION - Riesna Apramilda; Menhard Menhard; Rio Haribowo; Sukma Irdiana; Feby Arma Putra; Eko Nur Hermansyah (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the effect of service quality, key opinion leader strategy, and digital promotion on consumer repurchase intention in the context of digital business. In the era of digital transformation, companies increasingly rely on technology-based marketing strategies and social media to retain customers and increase repeat purchases. Two hundred people who have shopped online are surveyed for this quantitative study. Multiple linear regression techniques were employed for the data analysis. Concurrently, the data demonstrated that digital promotion, Key Opinion Leader approach, and service quality all significantly impact repurchase intention. One of the most important factors in determining whether or not a customer will buy from a company again is the key opinion leader approach. The results demonstrate the significant impact that public figures' trust and influence can have on consumers' perceptions and decisions. By emphasizing the importance of service quality and collaborating with relevant key opinion leaders, this study offers practical implications for online business actors looking to build efficient marketing strategies.